METHODICAL ASPECTS OF THE INDUSTRIAL BUSINESS VALUE MANAGEMENT - Y. Vorontsova (Вестник университета)
The article considers methodical approaches to the industrial business value management. The possibility of the value-oriented approach application for effective management of the indicators level, characterizing the industrial business value, has investigated. The concept «value-oriented management» specified by authors, has given. A set of estimated indicators, between which the narrowness of interrelation was defining, has offered, and their influence on business value has considered. A new paradigm utilization of the quantitative and qualitative indicators management, characterizing the industrial business value, is offering.